Safety management practices in the Malaysia Technical And Vocational Education Training (TVET) - Shafie, Ahmad Shafarin; Rubani, Siti Nur Kamariah; Paimin, Aini Nazura (2021)
For many years, the value of safety management practice has been the subject of research attention in many sectors in Malaysia in order to achieve a positive workplace safety climate. The practice of safety management among accredited centers in the education sector, however, has hardly been examined. This study was therefore conducted in Johor, Malaysia, to investigate the elements of the safety management practices in the Technical and Vocational Education Training (TVET). This research included seven participants consisting of safety and health (SH) coordinators from each accredited TVET center in Johor, Malaysia. Via interview data collection, this study used the full qualitative approach. The outcome of the thematic analysis showed that there are ten key elements of safety management practices that have become factors among accredited TVET centers in Johor, namely management commitment, safety policy, safety committee, instructor involvement, safety rules and procedure, safety training, safety audit, risk management, communication and feedback and also safety promotion. The accredited center is advised to pay attention to these ten elements in order to improve safety management practices in the TVET sector.